Ethanol in Fatal Road Traffic Accidents: The Prevalence of Ethanol in Fatal Road Traffic Accidents in The Bahamas: The Need for a Controlled Study - Davis, Danny; Ferguson, Veronica; Carey, James; Ferguson, Elburt Wesley (International Journal of Bahamian Studies, 2008)
There are no documented studies of the role of ethanol in fatal road traffic accidents in The Bahamas. This paper provides a retrospective analysis of the involvement of ethanol in road traffic fatalities for 2000-2002 in The Bahamas. In the three-year period covered by this study 185 traffic fatalities were recorded, post mortem blood samples from 139 decedents were analyzed for blood alcohol concentration (BAC). The involvement of ethanol in many of these fatalities was not conclusive because BAC at the time of the accident cannot be confidently extrapolated from post mortem BAC data. In an effort to understand the involvement of ethanol in road traffic accidents we propose that BAC of all participants in road traffic accidents involving injuries should be recorded. This proposal is based on, and supported by, the analyses of the available data. Analysis of the data highlights its deficiencies and that of the data collection system. The case for a systematic study is presented.